Electrical-based ultrafiltration processes enhanced by in-situ generation of Fe(III): Significance of permanganate oxidation. (June 2022) - Zhao, Jing; Wang, Jinlong; Lin, Dachao; Liu, Yatao; Zhang, Han; Tang, Xiaobin; Li, Guibai; Liang, Heng
Abstract: In this study, a permanganate-assisted electrocoagulation-ultrafiltration (PEC-UF) process was proposed to control membrane fouling in the treatment of secondary effluent. Four comparable systems, i.e., UF, electro-UF (E-UF), electrocoagulation-UF (EC-UF), and PEC-UF, were investigated to systematically clarify the role of permanganate and electrocoagulation in mitigating membrane fouling. Results revealed that the formation of a dense cake layer containing concentrated solutes was the primary reason for membrane fouling. Electrocoagulation significantly mitigated membrane fouling and resulted in the reduction of the normalized transmembrane pressure of the EC-UF and PEC-UF systems by 35.0% and 44.6% compared with the UF control system, respectively. However, the retention of a considerable amount of iron oxyhydroxide precipitates on the membrane surface aggravated inorganic fouling in the in-situ EC-UF system. Furthermore, the enhanced formation of Fe(III) by oxidation of Fe(II) with permanganate promoted the coagulation process. Hence, increased generation of Fe(III) and enhanced coagulation promoted by formed MnOx accelerated the formation of a hydrophilic cake layer with high porosity and thereby reduced the occurrence of both organic and inorganic membrane fouling. These results demonstrated the potential application of permanganate-assisted in-situ electrical-based methods to control UF membrane fouling during advanced wastewater treatment. Graphical abstract: Image 1 Highlights: Permanganate assisted electrocoagulation-UF (PEC-UF) was proposed. The formation of a dense cake layer was primary for UF fouling in water treatment. A high porous and hydrophilic cake layer was formed via Fe (Ⅲ) and MnOx in-situ. PEC-UF system displayed superior UF fouling control and organic removal behavior.